Percepce šátku mladých muslimek druhé generace v jejich východoevropské zkušenosti - Rendek, Zuzana (Lidé města, 2025)
This paper focuses on one of the religious practices of second-generation Muslim women in the Czech Republic, namely, wearing headscarves. I draw on Douglas’ theory of the dual body: the social body and the individual body. Society as a social body places limits/boundaries on the individual body and reflects its deviation from the norm. Considering the socio-cultural context of young Muslim women whose experience is influenced by dual biographies stemming from their their parents’ migrant background and from their socialization in Czech society, I ask how they negotiate the relevance of the headscarf in relation to their biographies, how they make decisions about their bodies in relation to putting on and wearing the headscarf, and how they reflect on how the headscarf completes their bodies. I gathered the data based on semi-structured interviews conducted between 2019 and 2024.